View of Nave and Apse - Ghosh, Ayan (2023)
St. Thomas Cathedral is the first Anglican church in Mumbai and one of the oldest structures within Bombay Fort. The church was built on an open space known as Bombay Green, which was later developed as Elphinstone Circle (Horniman Circle). The surrounding area is named Churchgate, after the city gate, which stood close to the church.